ANALISIS UNSUR INTRINSIK PUISI DALAM BUKU ANTOLOGI CERPEN DAN PUISI ANAK BALON KEINGINAN PENYUSUN KORRIE LAYUN RAMPAN DAN IMPLIKASI PEMBELAJARAN DI SD - Ilhami, Dina Rainida; Gunawan, Dani; Nuriyanti, Risma (caXra: Jurnal Pendidikan Sekolah Dasar, 2021)
Learning children's literature is an important part of the Indonesian language curriculum at elementary school level, aimed at developing appreciation for literary works and understanding everyday life through poetry. This research aims to analyze the intrinsic elements of children's poetry in the Anthology of Short Stories and Children's Poetry "The Balloon of Wishes" by Korrie Layun Rampan and its implications for learning in elementary schools. The research method used is descriptive qualitative with data collection techniques through document content analysis. The results of the research show that theme, tone, feeling and message are the dominant intrinsic elements in this children's poetry. The themes of love for the homeland, humanity and patriotism, as well as variations in tone such as advising, inviting, criticizing and expressing pride, anxiety, admiration, happiness and gratitude are an integral part of these poems. The messages delivered revolved around the importance of loving one's homeland, caring for others, and preserving the environment. The implication of this analysis is to increase students' understanding of life values ​​through poetry learning, which is expected to become a model for future literary research and support the development of a literacy culture in society